PARADIGMA SKEPTIS TERHADAP EKSISTENSI HISTORISITAS AL-QUR’AN PERSPEKTIF JOHN WANSBROUGH - Muhammad Syahrul Mubarak; Erina Aolia Pangesti (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
It has become vital in Western circles to discuss the study of the historical validity of the Qur'ān. Because it is considered unclear, it certainly originated from the main ideas of orientalists. Many Western scientists can position themselves when researching the Qur'an. The differences in views that occur among orientalists are due to generational dissimilarities. The difference that occurs is that there are outsiders in their research on the Qur'an departing from skepticism or doubt and not purely academic, so that it has the aim of discrediting Islamic teachings. One of the orientalist activists who had this attitude was John Wansbrough, who had doubts about the historicity of the Qur'ān. Thus, the purpose of this article is to explore everything related to the thoughts of John Wansbrough. This article uses the Library Research method, using journals and several other references in order to provide an explanation of orientalist figures, especially John Wansbrough. The results of this study reveal John Wansbrough's perspective and methodology in conducting studies on the Holy Qur'an.